2023
DOI: 10.5603/rpor.a2023.0019
|View full text |Cite
|
Sign up to set email alerts
|

Locally advanced non-small cell lung cancer: current issues and recent trends

Abstract: Considering that non-small cell lung cancer (NS-CLC) is the leading cause of cancer-related mortality [1], numerous clinical approaches have been implemented to enhance patient outcomes, including the combination of two oncologic procedures such as in the promising intraoperative radiotherapy, alongside the ongoing effort to establish a novel immunotherapeutic agent for NSCLC [2,3].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 105 publications
0
2
0
Order By: Relevance
“…Our findings suggest that for this population, PFS of the concurrent immunotherapy group was significantly longer than that of the consolidative immunotherapy group, especially among those who had a non-primary initial site of recurrence. The PACIFIC trial is the most widely recognized radioimmunotherapy combination therapy for NSCLC ( 12 ). The PACIFIC trial found that the use of durvalumab at the end of chemoradiotherapy provided robust and sustained OS compared to chemoradiotherapy alone (OS; 47.5 vs. 29.1 months; HR 0.72) and extensive PFS benefit (PFS: 16.9 vs. 5.9 months; HR 0.55), with 42.9% of patients remaining alive at 5 years ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that for this population, PFS of the concurrent immunotherapy group was significantly longer than that of the consolidative immunotherapy group, especially among those who had a non-primary initial site of recurrence. The PACIFIC trial is the most widely recognized radioimmunotherapy combination therapy for NSCLC ( 12 ). The PACIFIC trial found that the use of durvalumab at the end of chemoradiotherapy provided robust and sustained OS compared to chemoradiotherapy alone (OS; 47.5 vs. 29.1 months; HR 0.72) and extensive PFS benefit (PFS: 16.9 vs. 5.9 months; HR 0.55), with 42.9% of patients remaining alive at 5 years ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, histologic diagnosis is another method that can be implemented if the patient is suspected to have lung cancer. In a significant number of lung cancer patients, the tumor cells metastasize to other organs, largely to lymph nodes, bones, adrenal glands, and the brain [ 17 , 18 , 19 , 20 ]. Notably, the tumor type and stages of the cancer are used to determine the prognosis and treatment options [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%